THE LEVEL OF PARENTS' UNDERSTANDING REGARDING BALANCED NUTRITIONAL FOODS AMONG THE MOTHERS OF PKK SHAMARA 2 CIBEREM BANYUMAS - Sajawandi, Labib; Dewi Ambarwati; Desti Pujiati; Tatik Ariyati; Kasiro Fatmawati (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2024)
This research aims to determine parents' understanding of balanced nutrition, a study of mothers at PKK Shamara 2 Ciberem Banyumas. This research is based on initial observations by Posyandu administrators that the body weight of Per u m Shamara 2 children tends to decrease with age. This is based on the assumption that parents' preparation for MPASI does not follow the recommended principles of balanced nutrition. This research design is explained quantitatively. The method used is a survey. The population of this study consisted of mothers who were members of PKK Shamara 2, C iberem, and Banyumas. The total population was 35 parents. Data collection techniques used comprehension tests in the form of multiple-choice questions. Data analysis uses descriptive data presented in a percentage format. The research results show that parents generally have a fairly good understanding of nutritious foods that are appropriate for children's growth and development. Parents' knowledge about good eating patterns is influenced by parents' attitudes towards food consumption behavior that is not yet fully known, and secondly by the understanding that parents believe is related to that behavior or subjective norms of disapproval, and is explained from the perspective of a parent. Whether they can control behavior; Nutrition that suits your needs is also influenced by daily eating patterns, food preparation with unbalanced nutrition in its application, and determining food ingredients according to material and non-material conditions material from parents.